SIP-based IEEE802.21 media independent handover — a BT Intel collaboration - Choong, K. N.; Kesavan, V. S.; Ng, S. L.; Carvalho, F.; Low, A. L. Y.; Maciocco, C. (SPRINGER, 2007)
In this paper, we look at various mobility management protocols and handover frameworks in use in BT. We also report on the results from a collaborative proof of concept mixed network prototype for a seamless handover system using Intel's early implementation of the IEEE802.21 media-independent handover standard. The paper reports the design, implementation and deployment issues/options of a handover mechanism using the Intel framework which includes a connection manager and mixed network IEEE802.21 adaptation layer together with BT's SIP-based audio/video application in a heterogeneous Wi-Fi, WiMAX and Ethernet network environment.